Effectiveness of the ARTHE-e app for exercise adherence in people with knee osteoarthritis: protocol for a randomised controlled trial - Bruno Pereira; Charlotte Lanhers; Emmanuel Coudeyre; Lech Dobija; Mathilde Pelletier-Visa; Alexis Bonhomme (BMJ Open)
Introduction Osteoarthritis, the most prevalent joint disease, poses a significant challenge due to its progressive nature and impact on the whole joint and periarticular structures. Although exercise is crucial for symptom improvement and progression slowdown, adherence to exercise programmes remains a concern. In response, we have developed a novel smartphone-based m-health application, ARTH-e, specifically designed to enhance adherence to adapted physical activity in individuals with knee osteoarthritis. We aim to perform a prospective,multicenter, randomized (1:1) controlled trial to compare the effectiveness of m-health application ARTH-e (intervention group) with standard care (control group) on exercise adherence in people with knee osteoarthritis. We hypothesise that adherence will be stronger among users of the ARTH-e application.Methods and analysis We will recruit 120 participants from 5 hospitals in France. The participants will undergo a comprehensive assessment, including the Exercise Adherence Rating Scale (EARS) at 2, 4 and 6 months, Knee Injury and Osteoarthritis Outcome Score, Evaluation of the Perception of Physical Activity, Tampa Scale of Kinesiophobia, European Quality of Life 5 Dimensions and 3 Lines and a Visual Analogue Scale rating of pain at baseline and 6 months. Adherence will be monitored using a connected bracelet. The intervention group will use the ARTH-e application for 6 months, while the control group will follow stay-active advice from their physician. The primary outcome will be the difference between groups in the evolution of the EARS score at 6 months.Ethics and dissemination The study has been approved by the medical ethics committee (Comité de Protection des Personnes) XI of Saint Germain en Laye (27 March 2024) (ID for ethics approval: 24.00330.000201). Eligible individuals will sign the informed consent form before enrolment. Study results will be reported in peer-reviewed publications and at scientific meetings.Trial registration number NCT06359171.